The interaction between macroprudential and monetary policies: The cases of Norway and Sweden - Jin Cao; Valeriya Dinger; Anna Grodecka-Messi; Ragnar Enger Juelsrud; Xin Zhang (Norges Bank, 2020)
To shed light on the interaction between macroprudential and monetary policies, we study the inward transmission of foreign monetary policy in conjunction with domestic macroprudential and monetary policies in Norway and Sweden. Using detailed bank-level data we show how Norwegian and Swedish banks' lending reacts to monetary policy surprises arising abroad, controlling for the domestic macroprudential stance and the interaction between monetary and macroprudential policies. In both countries, the domestic macroprudential policy helps mitigate the effects arising after foreign monetary surprises.
hdl:11250/2677149
Keywords: E43; E52; E58; F34; F42; G21; G28; 330; monetary policy; macroprudential policy; policy interactions; bank lending; inwardtransmission; international bank lending channel